The challenges of conducting prehospital research: successes and lessons learnt from the Head Injury Transportation Straight to Neurosurgery (HITS-NS) trial. Issue 8 (8th January 2015) - McClelland, Graham; Pennington, Elspeth; Byers, Sonia; Russell, Wanda; Lecky, Fiona
Abstract : Head Injury Transportation Straight to Neurosurgery was a cluster randomised trial studying suspected severe head injury treatment pathways conducted in the North East Ambulance Service NHS Foundation Trust and North West Ambulance Service NHS Trust between January 2012 and March 2013. This was the world's first large scale trial of any trauma bypass and was conducted as a feasibility study. This short report will describe some of the lessons learnt during this ground breaking and complex trial.